Noctilucent Cloud in the Western Arctic in 2005: Simultaneous Lidar and Camera Observations and Analysis - Collins, R. L.; Taylor, Michael J.; Nielsen, K.; Mizutani, K.; Murayama, Y.; Sakanoi, K.; DeLand, M. T. (Journal of Atmospheric and Solar-Terrestrial Physics, 2008)
We report observations of a noctilucent cloud (NLC) over central Alaska by a ground-based lidar and camera on the night of 9–10 August 2005. The lidar at Poker Flat Research Range (PFRR), Chatanika (65°N, 147°W) measured a maximum integrated backscatter coefficient of 2.4×10−6 sr−1 with a peak backscatter coefficient of 2.6×10−9 m−1 sr−1 corresponding to an aerosol backscatter ratio of 120 at an altitude of 82.1 km. The camera at Donnelly Dome, 168 km southeast of PFRR, recorded an extensive NLC display across the sky with distinct filamentary features corresponding to wave structures measured by the lidar. The occurrence of the maximum integrated backscatter coefficient corresponded to the passage of a bright cloud band to the southwest over PFRR. The camera observations indicate that the cloud band had a horizontal width of 50 km and a length of 150 km. The horizontal scale of the cloud band was confirmed by medium-frequency radar wind measurements that reported mesopause region winds of 30 m/s to the southwest during the period when the cloud band passed over PFRR. Comparison of these measurements with current NLC microphysical models suggests a lower bound on the water vapor mixing ratio at 83 km of 7–9 ppmv and a cloud ice mass of 1.5–1.8×103 kg. Satellite measurements show that this NLC display occurred during a burst of cloud activity that began on 5 August and lasted for 10 days. This cloud appeared 10 days after a launch of the space shuttle. We discuss the appearance of NLCs in August over several years at this lower polar latitude site in terms of planetary wave activity and space shuttle launches.